Optimization of Biochar Production by Co-Torrefaction of Microalgae and Lignocellulosic Biomass Using Response Surface Methodology - Viegas, Catarina (2021)
ABSTRACT: Co-torrefaction of microalgae and lignocellulosic biomass was evaluated as a method to process microalgae sludge produced from various effluents and to obtain biochars with suitable properties for energy or material valorization. The influence of four independent variables on biochar yield and properties was evaluated by a set of experiments defined by response surface methodology (RSM). The biochars were characterized for proximate and ultimate composition, HHV, and methylene blue adsorption capacity. HHV of the biochars was positively correlated with carbonization temperature, residence time, and lignocellulosic biomass content in the feed. Co-torrefaction conditions that led to a higher yield of biochar (76.5%) with good calorific value (17.4 MJ Kg(-1)) were 250 & DEG;C, 60 min of residence time, 5% feed moisture, and 50% lignocellulosic biomass. The energy efficiency of the process was higher for lower temperatures (92.6%) but decreased abruptly with the increase of the moisture content of the feed mixture (16.9 to 57.3% for 70% moisture). Biochars produced using algal biomass grown in contaminated effluents presented high ash content and low calorific value. Dye removal efficiency by the produced biochars was tested, reaching 95% methylene blue adsorption capacity for the biochars produced with the least severe torrefaction conditions.Co-torrefaction of microalgae and lignocellulosic biomass was evaluated as a method to process microalgae sludge produced from various effluents and to obtain biochars with suitable properties for energy or material valorization. The influence of four independent variables on biochar yield and properties was evaluated by a set of experiments defined by response surface methodology (RSM). The biochars were characterized for proximate and ultimate composition, HHV, and methylene blue adsorption capacity. HHV of the biochars was positively correlated with carbonization temperature, residence time, and lignocellulosic biomass content in the feed. Co-torrefaction conditions that led to a higher yield of biochar (76.5%) with good calorific value (17.4 MJ Kg(-1)) were 250 & DEG;C, 60 min of residence time, 5% feed moisture, and 50% lignocellulosic biomass. The energy efficiency of the process was higher for lower temperatures (92.6%) but decreased abruptly with the increase of the moisture content of the feed mixture (16.9 to 57.3% for 70% moisture). Biochars produced using algal biomass grown in contaminated effluents presented high ash content and low calorific value. Dye removal efficiency by the produced biochars was tested, reaching 95% methylene blue adsorption capacity for the biochars produced with the least severe torrefaction conditions.